Experimental and/or genetically controlled alterations of the renal microsomal cytochrome P450 epoxygenase induce hypertension in rats fed a high salt diet. - K Makita; K Takahashi; A Karara; H R Jacobson; J R Falck; J H Capdevila (The Journal of Clinical Investigation, 1994)
Excess dietary salt induces a cytochrome P450 arachidonic acid epoxygenase isoform in rat kidneys (Capdevila, J. H., S. Wei, J. Yang, A. Karara, H. R. Jacobson, J. R. Falck, F. P. Guengerich, and R. N. Dubois. 1992. J. Biol. Chem. 267:21720-21726). Treatment of rats on a high salt diet with the epoxygenase inhibitor, clotrimazole, produces significant increases in mean arterial blood pressure (122 +/- 2 and 145 +/- 4 mmHg for salt and salt- and clotrimazole-treated rats, respectively). The salt- and clotrimazole-dependent hypertension is accompanied by reductions in the urinary excretion of epoxygenase metabolites and by a selective inhibition of the renal microsomal epoxygenase reaction. The prohypertensive effects of clotrimazole are readily reversed when either the salt or clotrimazole treatment is discontinued. The indication that a salt-inducible renal epoxygenase protects against hypertension, are supported by studies with the Dahl rat model of genetic salt-sensitive hypertension. Dahl resistant animals responded to excess dietary salt by inducing the activity of their kidney microsomal epoxygenase(s) (0.102 +/- 0.01 and 0.240 +/- 0.04 nmol of products formed/min per mg of microsomal protein for control and salt-treated rats, respectively). Despite severe hypertension during excess dietary salt intake (200 +/- 20 mmHg), Dahl salt-sensitive rats demonstrated no increase in renal epoxygenase activity. These studies indicate that acquired or inherited abnormalities in renal epoxygenase activities and/or regulation can be related to salt-sensitive hypertension in rodents. Studies on the human renal epoxygenase and its relationship to salt hypertension may prove useful.